Benefits, Facilitators, and Barriers of Alternative Models of Cardiac Rehabilitation: A QUALITATIVE SYSTEMATIC REVIEW. Issue 2 (10th March 2023) - Platz, Katherine; Kools, Susan; Howie-Esquivel, Jill
Abstract : We conducted a systematic review of qualitative studies examining patient perspectives of cardiac rehabilitation (CR) models that use either an alternative location (ie, home-based) and/or an alternative exercise. Benefits, facilitators, and barriers were reported by patients. These insights can help improve the delivery of CR and provide new directions for research. Abstract : Purpose: Cardiac rehabilitation (CR) improves health outcomes and quality of life for patients with cardiovascular disease, yet only a quarter of eligible patients enroll. A myriad of CR models that use either an alternative location (ie, home-based) and/or an alternative exercise have been developed to overcome known attendance and physical limitation barriers; however, patient experiences with these models have not been systematically reviewed. Our aim is to review patient experiences with these models of CR. Review Methods: We conducted a systematic review and thematic analysis of qualitative studies published between 2009 and January of 2022 from CINAHL, PubMed, Web of Science, and PsycINFO. Summary: Twenty-five studies were included, representing the perspectives of 487 individuals who participated in an alternative model of CR. Exercises included walking, tai chi, yoga, aquatic exercise, exergaming, chair-based exercises, aerobics, physical activity trackers, and individualized exercise plans. Nineteen of 25 studies used home-based models and two used live video. Twelve studies included patients with heart failure. Patient perspectives comprised three central themes: exercise benefits, exercise facilitators, and participation barriers. Some thematic categories were reported variably by particular model/study design (eg, home-based) than by others. All alternative models of CR were found to be physically, psychologically, and/or socially beneficial to patients. Participants described facilitators and barriers that were influential in the decision to initiate or continue exercise. These patient insights are critical for innovative delivery of CR that is appealing, accommodates physical limitations, and broadens access to improve health equity.